Seasonal activity of Mediterranean fruit fly (Ceratitis capitata) (Wiedemann 1824) Tephritidae in Fruit orchards around Benghazi city - Khadija Moftah El-shekhi; Prof. Abdalla Fadhl (Scientific Journal of University of Benghazi, 2026)
Seasonal incidence and activity of Medfly adults were monitored around Benghazi city at four different sites during the period from April to December 2010 using McPhail trap with pheromone and food attractants(ammonia salts solution 3% ) . Statistical analysis were applied to trap catches at different sites, the results indicated that there were significant differences in all trap catches between different areas (F = 14.405; df = 3; P= 0.000) and months (F = 2.017; df =8; P = 0.046). which might be due to changes in climatic conditions during study period and differences in host plant between areas.